Morphofunctional characteristics of flight-related traits in deltamethrin-resistant and susceptible Triatoma infestans (Klug, 1834) of the Argentinean Chaco - Víctor A. Maza; M. Victoria Cardinal; Julieta Nattero (Parasites & Vectors)
Abstract Background Chagas disease, transmitted by triatomine bugs, is a major vector-borne parasitic disease in Latin America. Triatoma infestans, the principal vector in the Southern Cone, is primarily controlled through residual insecticide spraying. However, resistance to pyrethroids, especially in Northern Argentina and Southern Bolivia, has emerged. Resistant T. infestans populations exhibit reduced fitness, including impacts on reproductive success and dispersal capacity. This study investigates the flight potential and morphological changes in T. infestans populations with varying levels of insecticide resistance, hypothesizing that resistance may induce morphological changes in wing and head structures related to dispersal. Methods We analyzed three resistance profiles of T. infestans—susceptible (S), moderately resistant (MR), and highly resistant (HR)—collected from ten domestic or peridomestic sites in two municipalities from Chaco province, Argentina. We registered flight muscle development and measured flight-related traits (wings, heads, and the stiff and membranous portions of the wing) using a landmark-based methodology. We also assessed morphological disparity and covariation of these traits across toxicological groups. Results Significant morphological differences were found between resistant and susceptible populations. The frequency of insects with and without muscle varied across toxicological groups only for females, exhibiting the highest proportion of HR insects with fight muscle (86.21%). MR and HR males exhibited smaller stiff portions of the wing and heads than S males. Shape variation analysis showed that S females had wider forewings than resistant females, while HR females had narrower wings with a wider stiff portion. Susceptible males had wider and longer wings compared with resistant groups. Additionally, resistant populations showed greater morphological disparity and reduced covariation between flight-related traits. Conclusions Our study shows that pyrethroid resistance in T. infestans is linked to morphological changes in flight-related traits. These changes suggest a tradeoff between resistance and flight capacity, with energy allocated to resistance mechanisms potentially limiting flight. The reduced covariation between flight traits in resistant individuals supports the idea of pleiotropic effects. While resistant individuals may perform better in insecticide treated areas, their reduced flight capacity could limit long-distance dispersal, affecting population dynamics and vector control efforts. Graphical abstract